Surface Observation Of Hollow Tube Mat After Sintering And Cutting Process - Abu Bakar, Mohd Hadzley; Raja Abdullah, Raja Izamshah; Md Ali, Mohd Amran; Yusoff, Wan Azahar; Wijeyesekera, Devapriya; Hasanah, Tuan Noor (Science International (Lahore), 2014)
-